La formalización de investigación preparatoria como causal de suspensión de la prescripción de la acción penal en relación a los principios que rigen el nuevo código procesal penal, en los dos últimos años de vigencia, en el distrito judicial de la libertad - Avalos Leiva, Deivis Joel (2013)
The way to overcome impunity for crimes as a keeper of Criminal Procedure , always latent in our legal system, always looking for the proper administration of justice within the parameters of due process , protected by all the safeguards and principles therein converges . For this reason the analysis of the Suspension of Prescription penal action becomes important in relation to the incorporation of Article 339° , subsection 1 of the Criminal Procedure Code in force since suspended the statute of limitations by the figure of the formalize the preliminary investigation unlimited . This particular research attempts to determine whether the application of this article violates procedural principles such as excessive delay or weapons Equal Rights Defense, knowing the criteria of interpretation of the rule in question and the basis for its application , in order to provide a proposal to amend the rule if it were necessary. It also resorted to legal instruments as compared Legislation, laws in force , Plenary Agreement; Doctrine and Jurisprudence in order to discern the proper application of this procedural rule . And in order to verify the analysis in this research surveys to lawyers , prosecutors and judges as Trujillo district headquarters of the Judicial District of La Libertad , obtaining salient data for our research was applied